Anomalous Fluctuation of Halogens in Relation to the Pollution Status along Lake Mariout, Egypt. (30th December 2020) - El-Said, Ghada F.; El Zokm, Gehan M.; El Sayed, Abeer A.; El Ashmawy, Ahmed A.; Shreadah, Mohamed A.
Abstract : This paper aimed to study the anomalous fluctuation of halogens with respect to the pollution status in surface water (w), pore water (p), and sediments (s) of Lake Mariout. It provided a framework for understanding the distribution of dissolved and precipitated halogen salts related to the pollution status of the lake. The study cleared out that bromide was only the most abundant halogen in the three studied partitions. On contrast, sediment's partition contained the lowest chloride content. Fluoride minerals, especially, fluorapatites and carbonate-fluorapatite (FAP and CFAP), had high Saturation Index (SI) values in surface water (42.77–51.95 and 16.04–60.89, respectively) and in pore water (51.26–54.60 and 17.52–78.33, respectively). Bromide and chloride were mainly found in the soluble forms in the surface water and pore waters. Iodide salts, (Ca(IO3 )2 and Ca(IO3 )2 .6H2 O), were moderately precipitated in surface and pore waters. Thus, SI content reflected that halogens, especially fluoride and iodide, played a vital role in reducing lake pollution. Fluorite (CaF2 ) and sellaïte (MgF2 ) could only be formed in pore water, while calcite and aragonite could be deposited from surface water. In addition, Cl was mainly found in the forms of NaCl, CaCl2, MgCl2, and KCl in surface and pore waters. The multivariate analysis revealed that fluoride precipitate may serve in decreasing the dissolved salt pollution. Multivariate analysis showed that in the long run, the fluoride precipitation in FAP and CFAP can significantly adsorb and absorb various pollutants and can protect the lake from pollution. The ecological risk assessment conducted by calculating the enrichment factor (EF) showed that the lake was still unpolluted. Regarding human health risks, at appropriate levels of human health and safety, the hazard quotient (HQ) and hazard index (HI) of halogens found to be lower than these reported levels. Hence, ingestion and dermal absorption routes of halogens by surface water and sediments did not pose any adverse effects to population reflecting uncontaminated status of Lake Mariout.